THE IDENTIFICATION OF REINFORCEMENT USED BY ENGLISH TEACHER FOR STUDENTS WITH AUTISM SPECTRUM DISORDER (ASD) - Supariani, Ni Ketut Lilis Ayu; Padmadewi, Ni Nyoman; Agustini, Dewa Ayu Eka (Universitas Pendidikan Ganesha, 2021)
Students who has special needs, need to be taught with special education. The fact is students with special education cannot put in the class with students in general school especially in the learning activity. One of the students with SEN that needs more attention during the classroom activity is Autism Spectrum Disorder (ASD). In this case, using kinds of reinforcements as a strategy to manage student’s behavior and also catch student’s attention during the learning process is needed. Therefore, this study aims to identify types of reinforcement usually used by the English teacher at SLB Negeri 1 Denpasar, in order to reveal what kind of reinforcement that usually used by the English Teacher for students with ASD and how the implementation of the reinforcement used. This research utilized a qualitative approach and descriptive method. The subject of this study was one English teacher at Sekolah Luar Biasa (SLB) Negeri 1 Denpasar. The data collection using reinforcement checklist, interview guide, and audio recording. This research showed, there are 3 types of reinforcement the teacher usually used, such positive verbal reinforcement, positive non-verbal reinforcement, and tangible reinforcement. The Implementation was looking at the students need such: attract students’ interest, appreciation and control students’ behavior.